Protective Film Formation on AA2024-T3 Aluminum Alloy by Leaching of Lithium Carbonate from an Organic Coating. Issue 3 (1st January 2016) - Liu, Yanwen; Visser, Peter; Zhou, Xiaorong; Lyon, Stuart B.; Hashimoto, Teruo; Curioni, Michele; Gholinia, Ali; Thompson, George E.; Smyth, Gerard; Gibbon, Simon R.; Graham, Derek; Mol, Johannes M. C.; et al.
Abstract : An investigation into corrosion inhibition properties of a primer coating containing lithium carbonate as corrosion inhibitive pigment for AA2024 aluminum alloy was conducted. It was found that, during neutral salt spray exposure, a protective film of about 0.2 to 1.5 μm thickness formed within the area where an artificial defect was introduced by scribing through the coating to the base alloy. This film showed a multilayered structure consisting of a relatively compact layer near the alloy substrate, a porous middle layer and a columnar outer layer. The thicknesses of the layers varied, as a consequence of the difference in the local concentration of lithium species leaching from the primer coating. The presence of the film in the scribed area significantly reduced corrosion of the alloy, with little consumption of the metal substrate within the scribed area during neutral salt spray exposure. Furthermore, the presence of the protective film resulted in a significant increase of impedance modulus, measured after the salt spray exposure.